THU0462 Increased Oxidative Stress and Macrophage Migration Inhibitory Factor in Patients with Familial Mediterranean Fever. (23rd January 2014) - Sari, I.; Savran, Y.; Kozaci, D. L.; Gunay, N.; Onen, F.; Akar, S.
Abstract : Background: Familial Mediterranean fever (FMF) is an autoinflammatory disorder characterized by recurrent, inflammatory, self-limited episodes of fever and serositis. Neutrophils are one of the key players in the pathophysiology of FMF. Macrophage migration inhibitory factor (MIF) is a pleiotropic cytokine involved in several inflammatory processes including innate and adaptive immune responses. In addition, MIF has been shown to regulate trafficking of inflammatory cells including neutrophils to the sites of inflammation. Because its association with innate immunity, leukocyte trafficking, and inflammation MIF may be considered as an attractive cytokine in the pathogenesis of FMF. In recent years, increasing attention has been focused on the role of oxidative stress in the pathogenesis of inflammatory rheumatic diseases. As neutrophils are one of the major sources for free radicals some researchers studied oxidative stress in FMF. Objectives: In this study we aimed to investigate MIF levels and its relationship with oxidative stress and M694V mutations in patients with FMF. Methods: Fifty one unrelated attack free FMF patients (14 M and 27 F, 32.8±8.7 years) and 30 healthy controls (16 M and 14 F, 32.7±7 years) were included in the study. Serum MIF were studied and allele frequency of M694V was calculated. Serum total oxidant status (TOS) and total anti-oxidant status (TAS) were also studied. Results: Age, sex distribution, anthropometrical indices, smoking status, serum lipids and TAS were similar between patients and controls. However; CRP, ESR, MIF, and TOS were significantly higher in the patients' group. Comparison of patients with and without M694V mutation revealed that MIF and TOS levels were not different between the groups. Regression analysis showed that none of the variables including disease duration, CRP, ESR, TOS, TAS and BMI were predicting MIF concentrations (P > 0.05) Conclusions: We found increased concentrations of MIF and oxidative stress in patients with FMF. Increased MIF levels were significantly correlated with oxidative stress and its levels were independent from the inflammatory activity. M694V mutations seem no effect on MIF and oxidative stress. Disclosure of Interest: None Declared